Pengaruh Penambahan Chorionic Gonadotrophin pada Medium Maturasi terhadap Kemampuan Maturasi, Fertilisasi, dan Perkembangan Embrio secara In Vitro Kambing Peranakan Ettawa (The Effect of Chorionic Gonadotrophin Addition Into Maturation Medium on The Abili - Nurvina Septi Adifa; Pudji Astuti; Diah Tri Widayati (Faculty of Animal Science, Universitas Gadjah Mada, 2010)
This research was conducted to investigate the effect of chorionic gonadotrophin addition into maturation medium on oocyte maturation, fertilization, and embryo development in vitro of Ettawa crossbred. Oocytes were divided into 3 groups, group I: maturation medium without addition of chorionic gonadotrophin (0), group II: 10 μl/10 ml chorionic gonadotrophin was added into maturation medium (1), group III: 20 μl/10 ml chorionic gonadotrophin was added into maturation medium (2). Oocytes were transferred into 50 μl maturation medium, then covered by mineral oil. Oocyte was incubated at 39oC, 5% CO2, 95% humidity for 24 hours for maturation. Matured oocytes were inseminated with frozen semen–thawed concentration 12.5 x 106/ml. Process of fertilization were carried out on incubator 39oC, 5% CO2, 95% humidity for 5 hours. The fertilized oocytes were transferred into 50 μl drop G–1, then incubated at 39oC, 5% CO2, 95% humidity. Embryo development was monitored every 24 hours. Culture medium was changed every 48 hours. G–2 medium used second day after culture. The variables measured involved oocyte maturation, fertilization, and in vitro cleavage rate. The data were analyzed by chi–square, using SPSS 15.0 program. The result showed no significant difference on the percentage of mature oocytes and fertilization rate were 78.0%, 72.8%, 75.0% and 76.6%, 74.5%, 77.8% respectively. But cleavage rate showed significant difference (P≤0.05) withthe values of 40.8%, 11.4%, and 12.2% respectively. Based on the result it could be concluded that chorionic gonadotrophin addition into maturation medium had not increased ettawa crossbred oocytes maturation, fertilization, and in vitro cleavage rate. The best maturation, fertilization, and in vitro cleavage rate were found using maturation medium without any addition of chorionic gonadotrophin.(Key words: Does oocyte, Chorionic gonadotrophin, In vitro maturation, In vitro fertilization, In vitro embryo development)